GENETIC RELATIONSHIP OF SEVERAL MORPHOLOGICAL AND MOLECULAR CHARACTERISTICS OF Phalaenopsis amabilis (L.) Blume ORCHIDS FROM THE MERATUS MOUNTAINS OF SOUTH KALIMANTAN, INDONESIA - Dindin Hidayatul Mursyidin; Muhammad Rubiansyah; Badruzsaufari Badruzsaufari (Indonesian Journal of Forestry Research, 2022)
Phalaenopsis amabilis (L.) Blume orchid is one of the most popular orchid species in the world. However, this ornamental plant is threatened in its natural habitat, the Meratus Mountains of South Kalimantan, Indonesia. This study determines and analyzes the genetic relationship among several morphological characteristics of P. amabilis from this region combined with molecular (RAPD) markers. A total of ten orchid samples comprised of nine moth orchids (P. amabilis) and one species (P. cornu-cervi) as an outgroup, as well as ten RAPD primers were used in this study. Based on the morphological markers, the moth orchids have a moderate level of genetic diversity, indicated by Shannon's index value of 0.5. In contrast to molecular markers, this germplasm shows high genetic polymorphism, shown by the polymorphism degree of 100% for all primers used. The cluster analysis shows that this germplasm can be divided into two clusters for morphological and five for molecular markers. Following these markers, the grouping of moth orchids was nearly corresponding to their origin. Thus, this information could be useful as a reference for orchid conservation and breeding programs in the future.